PENGARUH SUSUNAN SERAT TERHADAP SIFAT FISIK DAN MEKANIK KOMPOSIT HYBRID BERPENGUAT SERAT AGEL/FIBERGLASS MENGGUNAKAN TEKNIK VACUUM INFUSION - Hestiawan, Hendri; Zuliantoni; Saragih, Fernando Desfriandi (UNIB Press, 2024)
This research was motivated by using agel fiber which is easy to obtain and the effect of agel fiber which is hybridized using glass fiber using the vacuum infusion technique. This research aims to determine the effect of fiber arrangement on the mechanical and physical properties of agel/ fiberglass reinforced hybrid composite using the vacuum infusion technique. The main materials used in this research are agel fiber, fiberglass, ripoxy vinyl ester resin, methyl ethyl ketone peroxide (MEKP) catalyst and EX promoter. The process of making a specimen begins with preparing a mold from acrylic, then arranging the fibers based on predetermined variations in the arrangement. Resin, catalyst and promoter are mixed in a ratio of 400:40:1. Then stir until evenly mixed, then pour it into a container that is connected to the mold, after that the vacuum infusion process is carried out until the fiber structure in the mold is completely covered. The finished specimen is formed based on the testing standards. Bending test bending test uses ASTM D-790 standard, impact test uses ASTM D-5941 standard, tensile test uses ASTM D-638 standard, and density testing uses ASTM D-792 standard. The results of this research show that the mechanical and physical testing of the Agel-Gelas-Gelas-Gelas-Gelas-Gelas-Agel arrangement has the best bending strength, impact toughness and highest tensile strength, producing values ​​of 236.69 MPa, 62.97 kJ/ m2 and 84.1 MPa, while for testing the best density was obtained in the Gelas-Agel-Agel-Agel-Agel-Agel-Gelas G-5A-G arrangement of 1.19 gr/cm3.